Analysis of Selling Price Determination Using Cost Plus Pricing Method in Three Saudara Chicken Livestock Business, Selatan Bengkulu Regency - Rera Marsela; Sulisti Afriani; Yun Fitriano (Penerbit Jurnal Indonesia, 2022)
The purpose of the study was to determine and analyze the determination of the selling price using the Cost Plus Pricing Method in the Three Brothers Chicken Livestock Business, South Bengkulu Regency. The analytical method used in this study is a comparative descriptive method. Based on the calculation of the cost of production carried out by the Three Brothers Chicken Livestock Business, South Bengkulu Regency, the cost of production of broiler chickens per head is Rp. 32,238.-. and the determination of the selling price based on the market price of Rp. 38,000 per head so that the profit earned is Rp. 5,872 fish. Based on the cost plus pricing method with a full costing approach, the cost of production of broiler chickens is Rp. 33,418,-. With the determination of a profit of 20% of the cost of production, the total selling price of chicken per head is Rp. 40,000, - so that the profit earned is Rp. 6,582,- per head. There is a difference in the calculation of the cost of production between the company's calculation and the cost plus pricing method because the company's calculation does not include labor costs and factory overhead costs.